Pengaruh Bimbingan Konseling dalam Upaya Mengatasi Rendahnya Motivasi Belajar Matematika Siswa SMP - Christina Khaidir; Neviyarni Suhaili (Journal on Education, 2023)
The implementation of mathematics learning activities in schools often faces several obstacles. One of these obstacles is the low motivation to learn mathematics owned by students. Various things cause low motivation to learn mathematics, ranging from incompetent teachers, inadequate learning facilities and infrastructure, mathematical anxiety owned by students, and an unsupportive learning environment. Low learning motivation will result in low learning outcomes obtained by students. Counseling guidance is one of the solutions used to overcome the problem of low student motivation to learn mathematics. By using the literature review research method, this study aims to determine the increase in students' mathematics learning motivation if given counseling guidance. Articles were collected and selected by utilizing existing search engines. Inclusion criteria in this process include counseling guidance to increase motivation to learn mathematics, research on junior high school students, and conducted in Indonesia between 2013 and 2023. The results showed that by using counseling guidance, there was an increase in students' motivation to learn mathematics